Dimensions of remote learning during the Covid-19 pandemic in minority language schools - Zorčič, Sabina (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2020)
Based on a survey conducted among teachers in three schools in Austrian Carinthia where the language of instruction is (also) Slovene, the article examines the impact of remote learning between March and June - i.e. during the first wave of the Covid-19 pandemic - on a possible deterioration of students' language skills. The results also bring new data and insight into teachers' language accommodation. The results confirm the predominance of reading and writing communication with a minimum use of audio-video technology. The lower input of verbal communication mainly affected students with (strongly) unbalanced linguistic competence in both languages of instruction. Education is an important factor in reducing inequalities in society; thus, as long as remote learning increases inequality, this form of education should be pursued with some reservations.
Keywords: Avstrija; jezikovni vnos; jezikovno prilagajanje; koroški Slovenci; manjšinski jezik; pouk na daljavo; slovenska manjšina